Graphite tailing foam concrete as well as preparation method and application thereof

By using graphite tailings foam concrete, the problem of degradation of mechanical properties of foam concrete in the aircraft pavement barrier system under the influence of freeze-thaw cycle and climate change is solved, and higher water resistance, freezing resistance and stability are achieved, significantly improving The safety and effectiveness of the aircraft blocking system.

CN119430994APending Publication Date: 2025-02-14HEILONGJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411867607.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Under the influence of freeze-thaw cycle and climate change, foam concrete in existing aircraft pavement barrier systems is prone to cracks, pulverization and mechanical properties, resulting in reduced or failure of the barrier effect, increasing the aircraft's barrier distance and safety risks.

Method used

Graphite tailings are used as fine aggregate, combined with fast hard sulfaluminate cement, polypropylene fiber and specific additives, and the stress-crulling curve and collapse strength are adjusted to improve water resistance and Freeze resistance.

Benefits of technology

Graphite tailings foam concrete maintains good mechanical properties and durability under freeze-thaw cycle and climate change conditions. The rate of collapse strength changes within ±20%, the water absorption rate is less than 23%, and the freezing resistance coefficient is between 0.92 and 1.04 In between, the stability and safety of the aircraft road surface barrier system are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430994A_ABST
    Figure CN119430994A_ABST
Patent Text Reader

Abstract

The invention discloses graphite tailing foam concrete as well as a preparation method and application thereof, belongs to the technical field of aircraft pavement arresting systems, and aims to solve the technical problem that the mechanical property and durability of foam concrete are reduced due to freeze-thaw cycle. The preparation method of the graphite tailing foam concrete comprises the following steps: stirring and uniformly mixing the cement, the fine aggregate and the fiber to obtain a dry material; uniformly mixing a water reducing agent, a catalyst and water, adding the mixture into the dry material, stirring to obtain mixed slurry, adding a foaming agent and a foam stabilizer into the mixed slurry, stirring, adding a coagulation accelerator, and continuously stirring to obtain foam concrete slurry; and placing the foam concrete slurry in a mold, standing, removing the mold, and naturally curing to obtain the graphite tailing foam concrete. The graphite tailing foam concrete has water resistance, stable mechanical properties and good and stable energy absorption capacity, and meets the requirements of Characteristic Material Arresting System MH / T 5111-2015.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aircraft pavement arresting systems, and in particular relates to a graphite tailings foam concrete and a preparation method and application thereof. Background Art

[0002] Foamed concrete is widely used as a building thermal insulation and buffering material due to its low density, high porosity, excellent buffering and energy absorption effect, and adjustable strength. In recent years, in order to solve the problem of casualties and property losses caused by aircraft accidentally running off the runway, foamed concrete has begun to be used as an arresting material in the Engineered Material Arresting System (EMAS) to avoid the harm caused by aircraft running off the runway. The aircraft runway arresting system mainly uses foamed concrete (FC) as the core arresting material of the arrester. When the aircraft exceeds the limit and enters the EMAS, the arresting material is crushed to properly absorb the aircraft's kinetic energy.

[0003] At present, researchers at home and abroad are committed to developing foamed concrete with low density and high strength. However, foamed concrete used in aircraft pavement arresting systems must meet a specific strength range, good energy absorption characteristics and a certain degree of fragmentation. In order to ensure that foamed concrete maintains good arresting performance during the service life of EMAS and enhance the safety, effectiveness and designability of aircraft interception, the stress deviation of the platform section of the mechanical property curve (i.e., stress-crush curve) of foamed concrete during service must be stable within the design range of ±10% (Fang Jun. Preparation and performance research of ultra-lightweight concrete for aircraft arresting systems [D]. China Building Materials Science Research Institute, 2020.). When EMAS is rolled over by aircraft wheels, the arresting material (foam concrete) is compressed, crushed and compacted into powder. The compressive strength is not enough to characterize the compression process of the foam concrete in EMAS. The collapse strength (the average stress of the platform section of the stress-collapse curve) is needed to characterize the ability of the arresting material (foam concrete) to collapse and absorb energy after the aircraft wheel rolls over it. According to the "Characteristic Materials Arresting Systems" (MH / T 5111-2015), the collapse strength change rate of foam concrete during service should not be greater than 20%.

[0004] Although EMAS has been successful in engineering applications, the core arresting material foam concrete in the EMAS system will crack, powder and significantly reduce its mechanical properties due to the combined effects of airport climate temperature and rain and snow during the laying and service process, resulting in reduced or ineffective arresting effect. Sun Yumei et al. (Analysis of the Blocking Performance of the EMAS Core Layer under Freeze-Thaw Environment [D], Tianjin Polytechnic University, 2017) studied the performance of foam concrete in EMAS under freeze-thaw conditions and found that freeze-thaw cycles can cause the defects of the EMAS core layer to expand and gradually evolve into structural damage. These damages reduce the mechanical properties and durability of foam concrete, thereby increasing the aircraft arresting distance and increasing safety risks. Therefore, how to improve the durability and stable mechanical properties of foam concrete in EMAS has become a new research topic. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing graphite tailings foamed concrete.

[0006] Another object of the present invention is to provide graphite tailings foamed concrete obtained by the above preparation method.

[0007] Another object of the present invention is to provide application of the graphite tailings foamed concrete in an aircraft runway arresting system (EMAS).

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A method for preparing graphite tailings foamed concrete comprises the following steps: Step 1, stirring cement, fine aggregate and fiber until uniformly mixed to obtain dry material, wherein the ratio of cement, fine aggregate and fiber is (110-150): (80-120): (0.4-0.9) by weight, the cement is fast-hardening sulphoaluminate cement, the fine aggregate is graphite tailings, and the fiber is polypropylene fiber; In step 1, the stirring rate is 100-200 r / min, and the stirring time is 3-5 minutes.

[0010] Step 2, mixing the water reducer, the catalyst and water evenly, adding the mixture to the dry material, stirring to obtain a mixed slurry, adding a foaming agent and a foam stabilizer to the mixed slurry, stirring, adding a coagulant and continuing to stir to obtain a foamed concrete slurry, wherein the ratio of cement, water, water reducer, catalyst, foaming agent, foam stabilizer and coagulant is (110-150): (80-100): (1-2): (0.1-0.3): (5-6): (1.5-2.5): 8.58 by mass, the water reducer is a polycarboxylic acid water reducer, the catalyst is MnO2, the foaming agent is a hydrogen peroxide solution, the foam stabilizer is hydroxypropyl methylcellulose ether, and the coagulant is a J85 type coagulant; In step 2, the stirring rate is 150-400 r / min, and the stirring time is 1-10 minutes.

[0011] In step 2, the hydrogen peroxide solution is a mixture of hydrogen peroxide and water, and the concentration of hydrogen peroxide in the hydrogen peroxide solution is 20-40wt%.

[0012] Step 3, placing the foamed concrete slurry in a mold, leaving it to stand for at least 48 hours, removing the mold, and naturally curing it for at least 28 days to obtain graphite tailings foamed concrete.

[0013] The graphite tailings foamed concrete obtained by the above preparation method.

[0014] The above graphite tailings foamed concrete is used in the aircraft surface arresting system (EMAS).

[0015] In the above technical solution, the stress-crush curve platform section of the graphite tailings foam concrete Less than 10%, of which, is the maximum stress of the platform segment, is the average stress of the platform segment.

[0016] In the above technical solution, the stress-crush curve platform section of the graphite tailings foam concrete Greater than -10%, where is the minimum stress value of the platform segment.

[0017] In the above technical solution, the shrinkage strength change rate of the graphite tailings foam concrete is 15.8~17.6%.

[0018] In the above technical solution, the water absorption rate of the graphite tailings foam concrete is 23%.

[0019] In the above technical solution, the mass loss rate of the graphite tailings foam concrete after 25 freeze-thaw cycles is less than 3.5%, and the antifreeze coefficient is 0.92~1.04.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The graphite tailings foam concrete prepared by the present invention has water resistance, stable mechanical properties and good and stable energy absorption capacity, which meets the requirements of "Characteristic Material Arresting System" MH / T 5111-2015.

[0021] (2) The graphite tailings foam concrete of the present invention promotes the green, efficient, high-quality, high-value and large-scale utilization of graphite tailings, helps the construction of regional ecological civilization, and creates good ecological benefits.

[0022] (3) The graphite tailings foam concrete prepared by the present invention uses industrial solid waste graphite tailings as fine aggregate, which greatly reduces its cost and the treatment cost of tailings stacking, brings economic value to cities that develop with traditional resources, effectively saves energy and resources, increases industrial added value, and can create good social and economic benefits.

[0023] (4) Graphite tailings undergo crushing and grinding during the beneficiation process, which reduces their weight and increases their surface area. They are prone to flow and collapse when stored, causing vegetation damage and injuries, especially during the rainy season. They are prone to collapse and landslides. The resource utilization of graphite tailings can greatly reduce the occurrence of such safety accidents. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a photo of graphite tailings foam concrete; Figure 2 (a) is the stress-crush degree curve and energy absorption curve of the graphite tailings foamed concrete prepared in Examples 1 to 4, (b) is the stress-crush degree curve and energy absorption efficiency-crush degree curve of the graphite tailings foamed concrete prepared in Example 3; Figure 3 This is a SEM image of the graphite tailings foam concrete prepared in Example 1 after 25 freeze-thaw cycles; Figure 4 The morphology of the graphite tailings foam concrete prepared in Examples 1 to 4 after impact. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0026] Rapid hardening sulphoaluminate cement (grade 42.5R) was purchased from Tangshan Polar Bear Building Materials Co., Ltd.

[0027] The graphite tailings are produced in the mining area of ​​Xinghe County, Ulanqab City. The water content of graphite tailings is 2.52% and the density is 1800kg / m 3 , the chemical composition and content of graphite tailings are shown in Table 1; Table 1

[0028] The polypropylene fiber was purchased from Shuangsen Building Materials Co., Ltd. in Langfang City, Hebei Province. The single fiber length was 12 mm, the diameter of the polypropylene fiber was 6.57 μm, the tensile strength of the polypropylene fiber was 1.61 MPa, the elastic modulus of the polypropylene fiber was 42.13 GPa, and the elongation at break of the polypropylene fiber was 1.26%.

[0029] The polycarboxylic acid water reducer was purchased from Shaanxi Qinfen Building Materials Co., Ltd. The density of the polycarboxylic acid water reducer is 1100kg / m 3 The water reduction rate is 37%.

[0030] Manganese dioxide (MnO2) and hydrogen peroxide (H2O2) solutions were purchased from Tianjin Damao Chemical Reagent Factory. The concentration of hydrogen peroxide in the hydrogen peroxide (H2O2) solution was 30 wt%.

[0031] Hydroxypropyl methylcellulose ether (HPMC) was purchased from Shanghai Chenqi Chemical Technology Co., Ltd. The viscosity of hydroxypropyl methylcellulose ether was 200,000 and the fineness was greater than 80 mesh.

[0032] J85 type coagulant was purchased from Huaibei Xinda New Building Materials Co., Ltd.

[0033] In the following examples, a WGW-100G microcomputer-controlled universal testing machine is used to carry out a mechanical property test on graphite tailings foam concrete. The mechanical property test steps refer to "Characteristic Material Arresting System" (MH / T 5111-2015), and the loading rate of the WGW-100G microcomputer-controlled universal testing machine is set to 500 mm / min, and the maximum test force is 100 kN. Embodiment 1~4

[0034] A method for preparing graphite tailings foamed concrete comprises the following steps: Step 1, accurately weighing cement, fine aggregate and fiber with an electronic scale and placing them in a mixing bucket, stirring with a handheld mixer at 150 r / min for 4 minutes until they are evenly mixed to obtain a dry material, wherein the cement is fast-hardening sulphoaluminate cement, the fine aggregate is graphite tailings, and the fiber is polypropylene fiber, and the ratio of cement, fine aggregate and fiber is W by weight; Step 2, mixing the water reducer, the catalyst and water evenly, adding the mixture to the dry material, stirring at a uniform speed of 150 r / min for 10 minutes to obtain a uniformly mixed mixed slurry, adding a foaming agent and a foam stabilizer to the mixed slurry, stirring at a speed of 300 r / min for 1 minute, adding a coagulant and continuing to stir at a speed of 300 r / min for 1 minute to obtain a uniformly mixed foam concrete slurry, wherein the water reducer is a polycarboxylic acid water reducer, the catalyst is MnO2, the foaming agent is a hydrogen peroxide solution, the foam stabilizer is hydroxypropyl methylcellulose ether, and the coagulant is a J85 type coagulant. The ratio of cement, water, water reducer, catalyst, foaming agent, foam stabilizer and coagulant is 143:85.8:1.14:0.11:5.5:1.72:8.58 by mass; Step 3, placing the foamed concrete slurry in a 100 mm×100 mm×100 mm mold, removing the mold after standing for 48 hours, and naturally curing for 28 days to obtain graphite tailings foamed concrete.

[0035] The W and numbers of the graphite tailings foamed concrete prepared in Examples 1 to 4 are shown in Table 2.

[0036] Table 2

[0037] Figure 1 This is a photo of graphite tailings foam concrete. In the graphite tailings foam concrete, manganese dioxide is used as a catalyst to give full play to the foaming performance of hydrogen peroxide. Hydroxypropyl methylcellulose (HPMC) is used as a foam stabilizer to prevent the bubbles generated by the foaming agent from bursting prematurely and prolong the durability of the bubbles. A thin film can be formed at the interface between the foam concrete slurry and the bubbles. J85 type coagulant is used as a coagulant to harden the foam concrete in a short time, accelerate the stability of the bubble structure, and prevent the inconsistent coagulation and hardening rates of the inside and outside of the foam concrete slurry during coagulation and hardening, which leads to deformation of the internal and external structures of the graphite tailings foam concrete and the appearance of local fine cracks.

[0038] The test method for freeze-thaw resistance is as follows: The concrete was dried at 75°C and weighed as m1 (the density of the graphite tailings foam concrete was ρ1 at this time). The dried concrete was placed in a constant temperature and humidity chamber (temperature: 20±2°C, relative humidity: ≥90%) for 48 hours, taken out, the surface moisture of the concrete was absorbed, and the concrete was sealed in a plastic bag and subjected to N freeze-thaw cycles. After each freeze-thaw cycle, the concrete was taken out and dried to constant weight, and weighed as m2 (the density of the graphite tailings foam concrete was ρ2 at this time), wherein N is as shown in Table 3, the concrete is one of the graphite tailings foam concretes prepared in Examples 1 to 4, and each freeze-thaw cycle includes: the concrete sealed in the plastic bag is stored at -20±2°C for 6 hours, and then placed at room temperature for 5 hours.

[0039] m1 is the mass of graphite tailings foam concrete corresponding to N=0 in Table 3; m2 is the mass of graphite tailings foam concrete corresponding to N times in Table 3 after N times (N=5, 10, 15, 20 and 25) of freeze-thaw cycles.

[0040] ρ1 is the density of graphite tailings foam concrete corresponding to N = 0 in Table 3. ρ2 after N times (N = 5, 10, 15, 20 and 25) of freeze-thaw cycle operation is the density of graphite tailings foam concrete corresponding to N times in Table 3.

[0041] Mechanical properties tests were carried out on graphite tailings foam concrete (N=0) and graphite tailings foam concrete after N freeze-thaw cycles to obtain stress-crush curves. The collapse strength of graphite tailings foam concrete was obtained according to the stress-crush curves. The results are shown in Table 3. When N=0, the stress-crush curve of graphite tailings foam concrete is as follows Figure 2 As shown in (a).

[0042] Table 3

[0043] It can be seen from Table 3 that the collapse strength of the graphite tailings foam concrete prepared in Examples 1 to 4 increases first and then decreases with the increase in the proportion of graphite tailings. Among them, the graphite tailings foam concrete prepared in Examples 1 to 3 increases with the increase in the proportion of graphite tailings. The collapse strength is also increasing. At this time, the graphite tailings plays a skeleton role in the graphite tailings foam concrete, and its supporting role can be well reflected; when the proportion of graphite tailings in cement reaches 1.0 (graphite tailings foam concrete prepared in Example 4), the collapse strength of the graphite tailings foam concrete decreases, so the graphite tailings foam concrete prepared in Example 3 has the strongest collapse strength.

[0044] Further according to the mass loss rate formula and antifreeze coefficient formula of "Characteristic Material Arresting System" (MH / T 5111-2015), the mass loss rate (unit: %) and antifreeze coefficient of the graphite tailings foam concrete after 25 freeze-thaw cycles were calculated, as shown in Table 4. It can be seen from Table 4 that the mass loss rates of the graphite tailings foam concrete prepared in Examples 1 to 4 after 25 freeze-thaw cycles were less than 4%.

[0045] Table 4

[0046] Figure 2 (a) is the stress-crush curve and energy absorption curve of the graphite tailings foamed concrete prepared in Examples 1 to 4, Figure 2 It can be seen from (a) that in the mechanical properties test, as the externally applied penetration load increases and the penetration depth increases, the energy absorbed by the graphite tailings foam concrete prepared in Examples 1 to 4 gradually increases. In addition, the proportion of graphite tailings in the graphite tailings foam concrete prepared in Examples 1 to 4 also has a significant effect on the energy absorption capacity of the graphite tailings foam concrete. The energy absorption capacity shows a trend of first increasing and then decreasing with the increase of the proportion of graphite tailings. When the proportion of graphite tailings in cement is 0.8 (graphite tailings foam concrete prepared in Example 3), it reaches a peak value, that is, the graphite tailings foam concrete prepared in Example 3 has the strongest energy absorption capacity.

[0047] Figure 2 (b) is the stress-crush curve and energy absorption efficiency-crush curve of the graphite tailings foam concrete prepared in Example 3, Figure 2 From (b), it can be seen that the energy absorption efficiency of the graphite tailings foam concrete prepared in Example 3 is at its peak when the crushing degree reaches 70%, which meets the requirement of greater than 60% in "Characteristic Material Arresting System" MH / T 5111-2015.

[0048] The stress-crush curve obtained in the mechanical properties test can be divided into four stages: elastic deformation section, stress drop section, platform section and compaction section. In the platform section, the cell pores and cell walls at the fracture surface of the graphite tailings foam concrete gradually undergo obvious crushing and densification, resulting in local densification, which improves the bearing capacity of the graphite tailings foam concrete to a certain extent, thereby causing strain hardening. Therefore, in the entire platform section, the stress of the graphite tailings foam concrete shows different degrees of fluctuation, reflecting that the graphite tailings foam concrete has both strain softening and strain hardening behaviors, and its fluctuation phenomenon can also be regarded as the result of the alternating coupling of strain softening and strain hardening.

[0049] According to the stress-crush curve of graphite tailings foam concrete, the stress deviation is calculated by taking the stress of the platform section of the stress-crush curve, and the maximum value of the stress deviation of the platform section ( , is the maximum stress value of the platform segment) and the minimum stress value ( , The stability of each mechanical property curve (i.e., stress-collapse curve) of graphite tailings foam concrete at this N value is evaluated. At the same time, the change rate of collapse strength of graphite tailings foam concrete (N=0) and graphite tailings foam concrete after N times (N=5, 10, 15, 20 and 25) of freeze-thaw cycle operation is calculated. The calculation formula is as follows: ; ; in, η is the stress deviation, is the stress of the platform segment, is the average stress of the platform section (i.e., collapse strength); λ is the change rate of collapse strength, P N P0 is the collapse strength after N freeze-thaw cycles, and P0 is the collapse strength after 0 freeze-thaw cycles.

[0050] Graphite tailings foam concrete (N=0) and graphite tailings foam concrete after N freeze-thaw cycles η Maximum and η The minimum value and the change rate of collapse strength are shown in Table 5. It can be seen from Table 5 that within the operating range of 0 to 25 freeze-thaw cycles, the stress deviation of the platform section of the stress-collapse curve of the graphite tailings foam concrete prepared in Examples 2 to 3 is stable within the design range of ±10%, and the change rate of collapse strength after 25 freeze-thaw cycles is less than 20%, which meets the requirements of "Characteristic Material Arresting System" (MH / T5111-2015).

[0051] Table 5

[0052] Figure 3 The internal microscopic morphology of the graphite tailings foam concrete prepared in Example 1 after 25 freeze-thaw cycles is shown in FIG. Figure 3It can be seen that the pores of the graphite tailings foam concrete prepared in Example 1 present a needle-shaped crystal microstructure. This is because the finer graphite tailings in the graphite tailings foam concrete prepared in Example 1 play a filling effect, which not only enhances the fluidity of the slurry, but also reduces the collision damage of the graphite tailings foam concrete during the preparation process, thereby optimizing the pore structure of the graphite tailings foam concrete. In addition, the presence of a small amount of Al2O3 and CaO in the graphite tailings will produce a secondary hydration effect, and the generated hydrated gel product will fill the pore structure of the cement slurry after hardening, and interwoven needle-shaped crystals will appear, thereby improving the mechanical properties of the graphite tailings foam concrete.

[0053] Water resistance test: Place the concrete in an electric hot air drying oven (temperature 25±5℃) and dry it for 48 hours, then take it out and weigh it as m0. Soak the concrete in a water tank for 24 hours and ensure that the water level is 30mm above the top of the concrete. After soaking, take out the concrete and wipe the concrete surface with absorbent paper, then weigh it as m g , wherein the concrete is the graphite tailings foam concrete (N=0) prepared in Example 3, and its size is 100 mm×100 mm×100 mm.

[0054] Water absorption calculation formula: Water absorption = .

[0055] The water absorption rate of the graphite tailings foam concrete prepared in Example 3 is 23%.

[0056] Mechanical properties tests were performed on the graphite tailings foam concrete prepared in Example 3 that had undergone the "water resistance test" and the graphite tailings foam concrete prepared in Example 3 that had not been immersed in water. According to the semi-collapse energy and semi-collapse energy softening coefficient formulas in "Performance Material Arresting System" MH / T 5111-2015, the semi-collapse energy softening coefficient of the graphite tailings foam concrete prepared in Example 3 was calculated. The semi-collapse energy softening coefficient of the graphite tailings foam concrete prepared in Example 3 after immersion in water was 0.8, which still met the design requirement that the semi-collapse energy softening coefficient should be between 0.8 and 1.2 in "Performance Material Arresting System" MH / T 5111-2015. Therefore, the graphite tailings foam concrete prepared in Example 3 has water resistance.

[0057] The graphite tailings foamed concrete prepared in Examples 1 to 4 after 25 freeze-thaw cycles was subjected to SHPB impact test by ALT1000 Hopkinson bar test system, with impact speeds of 2m / s, 3m / s, 4m / s and 5m / s respectively. The incident bar and transmission bar of ALT1000 Hopkinson bar test system were hollow aluminum bars with a length of 2.5m and a diameter of 50mm. The size of the bullet in ALT1000 Hopkinson bar test system was 800mm in length and 50mm in diameter. Test results Figure 4 As shown by Figure 4 It can be seen that as the impact velocity increases, the graphite tailings foam concrete develops from block to powder after impact until it is completely crushed. In addition, when the impact velocity exceeds 4m / s, the morphology of the graphite tailings foam concrete after impact is not much different. As the proportion of graphite tailings increases, the degree of crushing of the graphite tailings foam concrete after impact is also different. When the proportion of graphite tailings is low, the graphite tailings foam concrete prepared in Examples 1 to 2 presents a fine powder at an impact velocity of 5m / s, and when the proportion of graphite tailings is high, the graphite tailings foam concrete prepared in Example 4 presents smaller particles at an impact velocity of 5m / s. The graphite tailings foam concrete prepared in Example 3 (the proportion of graphite tailings in cement is 0.8) can maintain good integrity when subjected to impact load, and the particle size is larger after impact crushing, and the impact resistance is the strongest, which is consistent with its mechanical properties.

[0058] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing graphite tailings foamed concrete, characterized in that: The following steps are involved: Step 1, stirring cement, fine aggregate and fiber until uniformly mixed to obtain dry material, wherein the ratio of cement, fine aggregate and fiber is (110-150): (80-120): (0.4-0.9) by weight, the cement is fast-hardening sulphoaluminate cement, the fine aggregate is graphite tailings, and the fiber is polypropylene fiber; Step 2, mixing the water reducer, the catalyst and water evenly, adding the mixture to the dry material, stirring to obtain a mixed slurry, adding a foaming agent and a foam stabilizer to the mixed slurry, stirring, adding a coagulant and continuing to stir to obtain a foamed concrete slurry, wherein the ratio of cement, water, water reducer, catalyst, foaming agent, foam stabilizer and coagulant is (110-150): (80-100): (1-2): (0.1-0.3): (5-6): (1.5-2.5): 8.58 by mass, the water reducer is a polycarboxylic acid water reducer, the catalyst is MnO2, the foaming agent is a hydrogen peroxide solution, the foam stabilizer is hydroxypropyl methylcellulose ether, and the coagulant is a J85 type coagulant; Step 3, placing the foamed concrete slurry in a mold, leaving it to stand for at least 48 hours, removing the mold, and naturally curing it for at least 28 days to obtain graphite tailings foamed concrete.

2. The preparation method according to claim 1, characterized in that: In step 1, the stirring rate is 100-200 r / min, and the stirring time is 3-5 minutes.

3. The preparation method according to claim 1, characterized in that: In step 2, the stirring rate is 150-400 r / min, and the stirring time is 1-10 minutes.

4. The preparation method according to claim 1, characterized in that: The hydrogen peroxide solution is a mixture of hydrogen peroxide and water, and the concentration of hydrogen peroxide in the hydrogen peroxide solution is 20-40wt%.

5. the graphite tailings foamed concrete that the preparation method described in any one of claims 1 to 4 obtains.

6. Application of the graphite tailings foamed concrete according to claim 5 in an aircraft pavement arresting system.

7. The use according to claim 6, characterized in that: The stress-crush curve platform section of the graphite tailings foam concrete Less than 10%, of which, is the maximum stress of the platform segment, is the average stress of the platform segment.

8. The use according to claim 6, characterized in that: The stress-crush curve platform section of the graphite tailings foam concrete Greater than -10%, where is the minimum stress value of the platform segment.

9. The use according to claim 6, characterized in that: The shrinkage strength variation rate of the graphite tailings foam concrete is 15.8-17.6%, and the water absorption rate of the graphite tailings foam concrete is 23%.

10. The use according to claim 6, characterized in that: The mass loss rate of the graphite tailings foam concrete after 25 freeze-thaw cycles is less than 3.5%, and the antifreeze coefficient is 0.92-1.04.

Citation Information

Patent Citations

  • Graphite tailing foam concrete and preparation method thereof

    CN111875405A